2020
DOI: 10.1186/s13024-020-00372-w
|View full text |Cite
|
Sign up to set email alerts
|

NLRP12 collaborates with NLRP3 and NLRC4 to promote pyroptosis inducing ganglion cell death of acute glaucoma

Abstract: Background: Acute glaucoma, characterized by a sudden elevation in intraocular pressure (IOP) and retinal ganglion cells (RGCs) death, is a major cause of irreversible blindness worldwide that lacks approved effective therapies, validated treatment targets and clear molecular mechanisms. We sought to explore the potential molecular mechanisms underlying the causal link between high IOP and glaucomatous RGCs death.Methods: A murine retinal ischemia/ reperfusion (RIR) model and an in vitro oxygen and glucose dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
79
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 74 publications
3
79
0
Order By: Relevance
“…These cleaved N-terminal GSDMD proteins accumulate in the plasma membrane and form pores, eventually leading to plasma membrane rupture and release of cytosolic contents (Kovacs and Miao, 2017). This study, together with our recently published study, provide compelling evidence that pyroptosis of activated microglia contributes to retinal ischemic injury, including the death of RGCs (Chen et al, 2020). We also found that both apoptosis and pyroptosis pathways were activated in OGDRstimulated microglia, and that the expression of pyroptotic marker proteins increased more rapidly than apoptotic marker proteins.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…These cleaved N-terminal GSDMD proteins accumulate in the plasma membrane and form pores, eventually leading to plasma membrane rupture and release of cytosolic contents (Kovacs and Miao, 2017). This study, together with our recently published study, provide compelling evidence that pyroptosis of activated microglia contributes to retinal ischemic injury, including the death of RGCs (Chen et al, 2020). We also found that both apoptosis and pyroptosis pathways were activated in OGDRstimulated microglia, and that the expression of pyroptotic marker proteins increased more rapidly than apoptotic marker proteins.…”
Section: Discussionsupporting
confidence: 69%
“…Mounting evidence implicates inflammasome-forming NLRs such as NLRP3, NLRP1, and NLRP6 in RIR injury (Chi et al, 2014;Wan et al, 2019), but the potential roles of regulatory NLRs have not been explored. By analyzing transcriptome sequencing data obtained from our recently published study (Chen et al, 2020), we discovered that the mRNA expression level of regulatory NLRC5 was significantly upregulated in the retina of RIR injury model mice, and this upregulation was further confirmed by RT-qPCR (Figures 1D,E). Both western blot and immunohistochemical staining also demonstrated significantly upregulated expression of NLRC5 in the retina at different times during reperfusion (Figures 1F-H).…”
Section: Nlrc5 Expression Is Markedly Elevated During Rir Injurymentioning
confidence: 65%
See 2 more Smart Citations
“…The N-terminal domain of cleaved GSDMD translocates to the cell membrane, forming the transmembrane pores that facilitate the release of cleaved IL-1β and IL-18, to stimulate in ammatory responses 23 . Accumulating evidence has shown that pyroptosis occurs in virous in ammatory diseases 24,25 , and our previous studies also found that pyroptosis participates in the pathological process of retina injuries following high IOP 18,26 . This study, for the rst time, found that IL-35 can lower the expression of in ammatory molecules and attenuate pyroptosis in vivo.…”
Section: Discussionsupporting
confidence: 52%